Eco-dyeing with biocolourant based on natural compounds. Issue 1 (24th January 2018) - Wang, Fubang; Gong, Jixian; Ren, Yanfei; Zhang, Jianfei
Abstract : Biomass pigments have been regarded as promising alternatives to conventional synthetic dyestuffs for the development of sustainable and clean dyeing. This investigation focused on in situ dyeing of fabrics with biopigments derived from tea polyphenols via non-enzymatic browning reaction. The average particle size of dyed residual liquor with natural tea polyphenol was 717.0 nm (ranging from 615.5 to 811.2 nm), and the Integ value of dyed wool fabrics was the greatest compared to those of counterparts. In addition, the Integ values of dyed fabrics with residual liquor were much bigger than those with the first reaction solutions when dyed by identical dyeing liquor. As a result, the dyeing process could be carried out many times because the concentration of the residual liquor was relatively superior. All dyed fabrics acquired admirable rubbing as well as washing fastness, and the relevant dyeing mechanism has been analysed in the paper.